Employee Performance Measurement through Balance Scorecard Instrument - Ratnawati, Susi; Rapitasari, Diana; Kharismawati, Ika; Negoro, RM Bramastyo Kusuma (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2020)
Balance Scorecard (BSC) is a score card for viewing and recording performance in an organization. Balance scorecard is used to measure executive performance and is a measurement tool for evaluating executive performance both financial and non-financial, in the short and long term, internal and external. Balanced Scorecard in its development not only relates to the card used to record executive scores but more broadly covers all lines. The results of research in the first year were the application of the BSC in the National Population and Family Planning Institution (BKKBN) starting in 2007 and up to now has experienced many improvements. BSC which was initially only applied for Echelon II levels, in 2009 was applied at echelon III and IV levels, then has also been applied at the staff level. The application of BSC in BKKBN is considered to have many benefits including being able to communicate organizational strategy from the highest level to the lowest level, providing an objective measure of employee performance appraisal, providing feedback to improve performance, and increasing leadership commitment to evaluate and improve performance.